Epigenetic dysregulation of autophagy in sepsis-induced acute kidney injury: the underlying mechanisms for renoprotection - Zhao, Shankun; Liao, Jian; Shen, Maolei; Li, Xin; Wu, Mei (Frontiers in Immunology, 2023)
Sepsis-induced acute kidney injury (SI-AKI), a common critically ill, represents one of the leading causes of global death. Emerging evidence reveals autophagy as a pivotal modulator of SI-AKI. Autophagy affects the cellular processes of renal lesions, including cell death, inﬂammation, and immune responses. Herein, we conducted a systematic and comprehensive review on the topic of the proposed roles of autophagy in SI-AKI. Forty-one relevant studies were finally included and further summarized and analyzed. This review revealed that a majority of included studies (24/41, 58.5%) showed an elevation of the autophagy level during SI-AKI, while 22% and 19.5% of the included studies reported an inhibition and an elevation at the early stage but a declination of renal autophagy in SI-AKI, respectively. Multiple intracellular signaling molecules and pathways targeting autophagy (e.g. mTOR, non-coding RNA, Sirtuins family, mitophagy, AMPK, ROS, NF-Κb, and Parkin) involved in the process of SI-AKI, exerting multiple biological effects on the kidney. Multiple treatment modalities (e.g. small molecule inhibitors, temsirolimus, rapamycin, polydatin, ascorbate, recombinant human erythropoietin, stem cells, Procyanidin B2, and dexmedetomidine) have been found to improve renal function, which may be attributed to the elevation of the autophagy level in SI-AKI. Though the exact roles of autophagy in SI-AKI have not been well elucidated, it may be implicated in preventing SI-AKI through various molecular pathways. Targeting the autophagy-associated proteins and pathways may hint towards a new prospective in the treatment of critically ill patients with SI-AKI, but more preclinical studies are still warranted to validate this hypothesis.